A Study on the Performance of Food Products of Kudumbashree Unit in Southern Kerala - P. , Jyothi; S Kumar, Rahul; S Kumar, Rohit; S Nair, Jayasrhee; Vahid, Ayida (International Journal of Psychosocial Rehabilitation, 2020)
Kudumbashree is a program organized by the government of Kerala for the upliftment of women in rural areas. This program helps women to increase their ability and talent and introduce their ideas in different fields in developing society. Kudumbashree has a three-tier structure for its women’s community network, with neighborhood groups at the lower level, area development societies at the middle level, and community development societies at the government level. The aim of the study is to know the economic empowerment of women and their financial support from the government. The study is conducted on five units in each district of southern Kerala, which are Thiruvananthapuram, Kollam, and Alappuzha. This study helps us to understand the financial enhancement of women working under the Kudumbashree unit, and it also helps us to ensure a minimum standard of living.